"Making Moves" in a Cardiac ICU: An Epistemology of Rhythm, Data Richness, and Process Certainty. (7th January 2020) - Stonington, Scott D.
Abstract: Ethnographers of clinical rationality often assume that the goal of biomedical practice is to eliminate uncertainty to produce definitive diagnoses. In this ethnography of an academic cardiac intensive care unit (CCU) in the United States, bodies are conceived instead as ever‐changing constellations of problems that make diagnostic certainty irrelevant and require clinicians to construct and reconstruct temporary models to facilitate action. They suspend their uncertainty to "convince themselves" enough to "make moves" on patients, driven by the relentless tempo of critical illness. This necessitates a practice‐oriented model of professional rationality that can account for the flow of time, with implications beyond the biomedical.